PROGRAM PELATIHAN PENIGKATAN KEMAMPUAN BAHASA INGGRIS ANAK-ANAK PANTI ASUHAN MELALUI PEMBERDAYAAN MAHASISWA - Jaka Satria Warman; Vivi Mardian; Laila Suryani; Fina Rahayu Fista; Irwan Irwan (Universitas Lancang Kuning, 2019)
The ability to master English is highly essential in this modern era because English is not only used in academic field, but also in the workplace. However, many Indonesian people still have low English skills especially those who come from disadvantaged group like orphans. On the other side, many university students nowadays contribute less to society. One of the causes might be because of the lack of platforms by which they can contribute to. Therefore, the team initiated training program to improve English skills for orphans through the empowerment of university students. The training program was conducted at Al-Falah Orphanage Padang and there were 24 orphans and 10 students involved. The training consisted of 16 meetings and each meeting lasted for about 90 – 120 minutes. The team employed five teaching methods that were combined and modified. The data were obtained from pre- and post test and class observation. The result showed that the orphans’ English ability increased from the mean of 42.8 to 69.5. In addition, there was an increase in their reading and speaking skills as well as their motivation in learning English. Moreover, this program also benefitted both parties inveolved (orphans and students) socially, economically and educationally. This means that there was a significant positive impact after the implementation of this program. Therefore, it is highly recommended to conduct the same program.